First-principles study of acceptor Li/Ag/Cu doping and Zn vacancy on the magnetic mechanism of ZnO and the universality of itinerant electrons. (March 2021) - Hou, Qingyu; Sha, Shulin
Abstract: Li/Ag/Cu doping and Zn vacancies have been theoretically and experimentally shown to induce ZnO to have room-temperature ferromagnetism. However, the source and mechanism of magnetic properties of such doped systems remain unclear. Previous researchers believe that all oxygen ions are negative divalent ions, as the basic assumption of the double-exchange interaction model, but no reasonable theoretical explanation has been put forward. Experimental control of Zn vacancies in ZnO is also challenging, but first principles can solve such problems. In this work, based on the generalized gradient approximation plane wave ultrasoft pseudopotential + U method under the framework of spin density functional theory, we used first principles to study the effect of the magnetic source and mechanism of Li/Ag/Cu doping and Zn vacancy on ZnO. We found that in addition to O 2– ions, some O 1– ions also existed in all doping systems. These ions had the dual-nature universality of itinerant electrons (donors) and local electrons (acceptors). The itinerant electrons in the Zn14 LiO16, Zn14 AgO16, and Zn14 CuO16 systems further possessed the same spin. Compared with Zn14 LiO16, Zn14 AgO16, and Zn14 CuO16 systems under the same doping amount, our results showed that the magnetic properties of Zn28 Li2 O32, Zn28 Ag2 O32, and Zn28 Cu2 O32 systems all increased. The Zn28 Li2 O32 system was found to be highly advantageous as a ferromagnetic functional material, which can guide the study of the magnetic source and mechanism of ZnO and similar oxide semiconductors through itinerant electrons.